Reinventing institutions: Trust offices and the Dutch financial system, 1690s-2000s - Abe de Jong; Joost Jonker; Ailsa Röell; Gerarda Westerhuis (The European Association for Banking and Financial History (EABH), 2020)
Trust offices (administratiekantoren) that repackage securities have been a central institution in Dutch finance since the late eighteenth century. Their basic form and functioning have remained largely the same, but over time, the repackaging has come to serve a variety of very different purposes. We argue that trust offices have been reinvented several times to adapt to changing circumstances. Originally set up for administrative convenience, they helped to create liquidity, notably for foreign securities. As from the 1930s, their most prominent purpose became to shield directors of large corporation from shareholder influence and hostile takeover threats. This is still their most common function in their current reincarnation as dedicated foundations, each tied to a particular company and largely controlled by its board and executives.
Keywords: G23; N23; N24; 330; trust offices; corporate governance; financial innovation; the Netherlands